2006
DOI: 10.1002/hbm.20220
|View full text |Cite
|
Sign up to set email alerts
|

Coherent corticomuscular oscillations originate from primary motor cortex: Evidence from patients with early brain lesions

Abstract: Coherent oscillations of neurons in the primary motor cortex (M1) have been shown to be involved in the corticospinal control of muscle activity. This interaction between M1 and muscle can be measured by the analysis of corticomuscular coherence in the beta-frequency range (beta-CMCoh; 14-30 Hz). Largely based on magnetoencephalographic (MEG) source-modeling data, it is widely assumed that beta-CMCoh reflects direct coupling between M1 and muscle. Deafferentation is capable of modulating beta-CMCoh, however, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
64
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 38 publications
(72 reference statements)
3
64
0
Order By: Relevance
“…This was identical to the time lag that was found in the beta band during static force output. An 11-ms time lag for the beta band is consistent with previously findings, e.g., 15.9 ms (Mima et al, 2000), 9.3 ms (Gerlo↵ et al, 2006) and 7.9 ms (Witham et al, 2011). Similarly, (Scho↵elen et al, 2005) found a positive slope for corticomuscular gamma-band coherence corresponding to a time delay of 7.0 ms.…”
Section: Discussionsupporting
confidence: 91%
“…This was identical to the time lag that was found in the beta band during static force output. An 11-ms time lag for the beta band is consistent with previously findings, e.g., 15.9 ms (Mima et al, 2000), 9.3 ms (Gerlo↵ et al, 2006) and 7.9 ms (Witham et al, 2011). Similarly, (Scho↵elen et al, 2005) found a positive slope for corticomuscular gamma-band coherence corresponding to a time delay of 7.0 ms.…”
Section: Discussionsupporting
confidence: 91%
“…Persistence of fast-conducting ipsilateral corticospinal projections from the noninfarcted motor cortex, which normally would have been withdrawn during development, 4 and focal corticomuscular coherence over the ipsilateral motor cortex have been demonstrated previously. 6 That the contralateral occipital cortex can also control movement of the paretic hand has not been reported previously in humans or animal models. Therefore, excitation of brainstem motor pathways is an unlikely explanation for our findings, because they lie too far below the scalp to be excited directly and, with the exception of the rubrospinal pathway, which is virtually absent in the human brain, 10 innervate the spinal cord and excite muscles bilaterally.…”
Section: Discussionmentioning
confidence: 96%
“…Although afferent inflow may modulate beta-range CMC, our results reconcile the view that the efferent motor information alone is sufficient to generate beta-band CMC during steady-state force. Recently Gerloff et al (2006), by clearly identifying the primary motor and somatosensory cortex in patients with early brain lesions, also provided evidence that beta-range CMC represents efferent drive from the primary motor and not reafferent feedback processing. This is also in line with Farmer et al (1993), who studied synchronization between single motor units in the first dorsal interosseous muscle of the dominant (right) hand of another deafferented patient (IW) and did not report any FIG.…”
Section: Discussionmentioning
confidence: 99%